2020
DOI: 10.1177/1932296820936224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Opportunities and Limitations of Mid-Infrared Skin Spectroscopy for Noninvasive Blood Glucose Monitoring

Abstract: Background: A wide range of optical techniques has recently been presented for the development of noninvasive methods for blood glucose sensing based on multivariate skin spectrum analysis, and most recent studies are reviewed in short by us. The vibrational spectral fingerprints of glucose, as especially found in the mid-infrared or Raman spectrum, have been suggested for achieving largest selectivity for the development of noninvasive blood glucose methods. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Glucose sensing in the MIR has been demonstrated in aqueous solution, serum and human subjects [44,45] using MIR quantum cascade lasers, and it was found that 84% of results were within the clinically acceptable region of the Clarke analysis grid [46]. Attenuated total reflection (ATR) MIR was used with a three-wavelength model to obtain high accuracy results in the Clarke grid [47], however, another study found that ATR was unlikely to be effective due to the poor penetration of MIR light (up to 10 µm) and further confounding factors [48]. The penetration depth of MIR and the consequently short path length is the primary limitation of this wavelength range compared to the near infrared region.…”
Section: Mid Infrared Spectroscopymentioning
confidence: 99%
“…Glucose sensing in the MIR has been demonstrated in aqueous solution, serum and human subjects [44,45] using MIR quantum cascade lasers, and it was found that 84% of results were within the clinically acceptable region of the Clarke analysis grid [46]. Attenuated total reflection (ATR) MIR was used with a three-wavelength model to obtain high accuracy results in the Clarke grid [47], however, another study found that ATR was unlikely to be effective due to the poor penetration of MIR light (up to 10 µm) and further confounding factors [48]. The penetration depth of MIR and the consequently short path length is the primary limitation of this wavelength range compared to the near infrared region.…”
Section: Mid Infrared Spectroscopymentioning
confidence: 99%
“…Another device (under development in Tohoku University, Japan) is a minimally invasive device applicable on the inner lips, harnessing an attenuated total internal multireflection geometry ( Kino et al, 2016 ; Villena Gonzales et al, 2019 ). However, the use of attenuated total reflection for this kind of measures has been criticized due to penetration depth limitations ( Delbeck and Heise, 2021 ).…”
Section: Blood Glucose Monitoring Devicesmentioning
confidence: 99%
“…The required penetration depths for glucose detection are obtained using a quantum cascade laser (QCL), a semiconductor material divided into injecting and active regions [5]. Delbeck and Heise [13] presented their research based on a multivariate skin spectrum analysis. To achieve the largest selectivity for the development of non-invasive blood glucose method, they used the vibrational spectral fingerprint of glucose that is usually found in Mid-infrared spectroscopy.…”
Section: Mid-infrared Spectroscopymentioning
confidence: 99%